2018
DOI: 10.1080/03004279.2018.1429479
|View full text |Cite
|
Sign up to set email alerts
|

Curiosity killed by SATs: an investigation of mathematics lessons within an English primary school

Abstract: By taking both pupils' and teachers' actions as the point of departure, this study aimed to understand governance within a primary school classroom. Video footage was recorded in an English primary school in which mathematics happened to be the focus. This data was analysed to identify the directions of both governance and self-governance and to help understand the consequences for pupil and teacher subjectivities. Our findings revealed the central role of national testing and inspection policy in constituting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The absence of play from the infant school classrooms in which I work serve to produce particular kinds of students ready to work to the rigid timetables necessary to get through the curriculum content set down. In line with other state schools in the UK (Ward & Quennerstedt, 2019;West, 2010) from year one onwards at Greenfield, the teachers and students work to timetables which reflect the hierarchy of curriculum subjects in terms of numbers of hours allocated to them and the time in the day in which they are taught. Thus, mornings are given over to English and maths whilst the humanities, science, music, PE, and art are taught in afternoons.…”
Section: The Appearance Of Play In An In-between Moment Of Transitionmentioning
confidence: 96%
“…The absence of play from the infant school classrooms in which I work serve to produce particular kinds of students ready to work to the rigid timetables necessary to get through the curriculum content set down. In line with other state schools in the UK (Ward & Quennerstedt, 2019;West, 2010) from year one onwards at Greenfield, the teachers and students work to timetables which reflect the hierarchy of curriculum subjects in terms of numbers of hours allocated to them and the time in the day in which they are taught. Thus, mornings are given over to English and maths whilst the humanities, science, music, PE, and art are taught in afternoons.…”
Section: The Appearance Of Play In An In-between Moment Of Transitionmentioning
confidence: 96%
“…International research on high stakes testing has suggested a variety of impacts on all areas of schooling, from teacher professionalism and subjectivities, to pedagogy and practice (Bibby 2009;Booher-Jennings 2008;Hall et al 2004;Keddie 2016;Reay and Wiliam 1999;Torrance 2017;Ward and Quennerstedt 2019). A variety of effects has been noted relating to how teachers organise and teach children in their classrooms over the last nearly three decades of national curriculum assessments in England.…”
Section: The Relationship Between Assessment and Pedagogic Practicementioning
confidence: 99%
“…There may also be crowding out of activities that are not measured. Public examinations may encourage schools to ‘teach to the test’, thus reducing attention to other non‐measured educational opportunities (Ward and Quennerstedt, ). The EBacc indicator, which holds schools to account for pupils’ achievement in specified core academic subjects, has been found to reduce schools’ focus on physical education (Maguire, Gewirtz, Towers, et al., ).…”
Section: Accountability and Behaviourmentioning
confidence: 99%